Milking Biosecurity in Dairy Cattle Farming East Java Indonesia - Kristanti, Novita Dewi; Fernandes, L.Nabilsy Maulana Yusuf; Windari , Wahyu; ShikhMaidin, Mashitah (Journal of Agriprecision & Social Impact, 2024)
This study aims to determine the quality of microorganisms and the chemical quality of milk before and after counseling, as well as farmers' attitudes regarding biosecurity in dairy farming businesses in East Java, Indonesia. Milk samples were collected from 30 dairy farmers to determine microbial and chemical quality. Paired samples T test and Wilcoxon test were used to assess attitudes after counseling. The milk tested for reductase is grade 2 milk with microorganism contamination of 500,000 – 4,000,000 cells/ml. Test results using lactoscan contained FAT 1.03%, SNF 9.47%, Density 30.06 g/ml Lactose 5.23%, Salt 0.72%, Protein 3.35%, Temperature 28.32º F and pH 5.27. The content of microorganisms decreased after the counseling was carried out. Farmers' attitudes regarding the implementation of milking biosecurity in dairy farming businesses received a T score of >50, which means that 19 people or 63% of the total respondents had a positive attitude tendency.